Paradoxical and bidirectional drug effects - Smith, S; Smith, S; Hauben, M; Hauben, M; Hauben, M; Hauben, M; Aronson, J (2012)
A paradoxical drug reaction constitutes an outcome that is opposite from the outcome that would be expected from the drugs known actions. There are three types: 1. A paradoxical response in a condition for which the drug is being explicitly prescribed. 2. Paradoxical precipitation of a condition for which the drug is indicated, when the drug is being used for an alternative indication. 3. Effects that are paradoxical in relation to an aspect of the pharmacology of the drug but unrelated to the usual indication.In bidirectional drug reactions, a drug may produce opposite effects, either in the same or different individuals, the effects usually being different from the expected beneficial effect. Paradoxical and bidirectional drug effects can sometimes be harnessed for benefit; some may be adverse. Such reactions arise in a wide variety of drug classes. Some are common; others are reported in single case reports. Paradoxical effects are often adverse, since they are opposite the direction of the expected effect. They may complicate the assessment of adverse drug reactions, pharmacovigilance, and clinical management. Bidirectional effects may be clinically useful or adverse. From a clinical toxicological perspective, altered pharmacokinetics or pharmacodynamics in overdose may exacerbate paradoxical and bidirectional effects. Certain antidotes have paradoxical attributes, complicating management. Apparent clinical paradoxical or bidirectional effects and reactions ensue when conflicts arise at different levels in self-regulating biological systems, as complexity increases from subcellular components, such as receptors, to cells, tissues, organs, and the whole individual. These may be incompletely understood. Mechanisms of such effects include different actions at the same receptor, owing to changes with time and downstream effects; stereochemical effects; multiple receptor targets with or without associated temporal effects; antibody-mediated reactions; three-dimensional architectural constraints; pharmacokinetic competing compartment effects; disruption and non-linear effects in oscillating systems, systemic overcompensation, and other higher-level feedback mechanisms and feedback response loops at multiple levels. Here we review and provide a compendium of multiple class effects and individual reactions, relevant mechanisms, and specific clinical toxicological considerations of antibiotics, immune modulators, antineoplastic drugs, and cardiovascular, CNS, dermal, endocrine, musculoskeletal, gastrointestinal, haematological, respiratory, and psychotropic agents. © 2012 Adis Data Information BV. All rights reserved.